Biomassa dan Cadangan Karbon Tiga Jenis Tumbuhan Herba (Cyclosorus interruptus, Nephrolepis biserrata, dan Digitaria didactyla) pada Periode Penyiangan Berbeda - Eni Susanti; Karyati Karyati; Muhammad Syafrudin (Fakultas Kehutanan Universitas Mulawarman, 2021)
The weeding duration influences the biomass and carbon content of herbaceous species. The objective of this study was to analyze the biomass and carbon content of three herbaceous species (Cyclosorus interruptus, Nephrolepis biserrata, and Digitaria didactyla) in terms of different wedding durations. The biomass of Cyclosorus interruptus that weeded for 2, 3, and 4 weeks were 26.50 grams, 35.50 grams, and 27.00 grams in a study plot sized 12 m2. Nephrolepis biserrata had biomass of 15.38 grams (weeding period of 2 weeks), 15.28 grams (weeding period of 3 weeks), and 19.90 grams (weeding period of 4 weeks). The biomass content of Digitaria didactyla were 76.67 grams, 74.00 grams, and 190.00 grams for weeding periods 2, 3, and 4 weeks, respectively. The carbon content of Cyclosorus interruptus with weeding periods of 2, 3, and 4 weeks were 0.062 tons/ha, 0.056 tons/ha, and 0.032 tons/ha, respectively. Nephrolepis biserrata had carbon contents of 0.067 tons/ha, 0.051 tons/ha, and 0.050 tons/ha in weeding periods 2, 3, and 4 weeks. Digitaria didactyla with the highest carbon content was weeded every 4 weeks (0.223 tons/ha), compared to weeding periods of 2 weeks (0.180 tons/ha) and 3 weeks (0.116 tons/ha).